(untitled) (Nigerian Journal of Technology, 2024)
The research paper investigates the impact of fire on concrete structures, focusing on evaluating the temperatures reached during the fire using the colorimetry test method. It examines color changes as indicators of temperature, assesses the extent of damage to building components, and determines the depth of carbon penetration within the structure. The study employs various assessment techniques, including rebound hammer test, colorimetry test to evaluate structural integrity post-fire. Key findings include the correlation between color changes and temperature, the effectiveness of rebound hammer tests in assessing structural integrity, and the importance of considering aggregate type in color analysis. The study was conducted using prescribed non-destructive testing (NDT) techniques. For the investigation of the fire-damaged building, the Rebound number (RN) values were used to correlate the in-situ compressive strength of concrete using the standard curves developed in the laboratory for this purpose. Moreover, the approximate temperature to which any structural element had reached was determined approximately by colorimetry test. Further the residual compressive strength of concrete of these elements was also derived applying the reduction factors in Eurocode 2 for concrete exposed to varied temperatures. The maximum percentage difference between these two sets of values was 15.46% except for one case. The residual strength values of concrete of the structural elements paved a way for satisfactory evaluation of the need of retrofitting of these elements, Overall, the research offers practical insights for assessing the residual compressive strength of concrete of structural elements of fire-damaged concrete structures by two different techniques thus aiding in decision-making for rehabilitation or reconstruction efforts of such structures.